Pengaruh Lingkungan Kerja Dan Kompensasi Terhadap Loyalitas Karyawan Di PT. Nawakara Arta Kencana Jakarta - Tungga Buana Irfana; Wiryo Harto Kusuma (Pusat Riset dan Inovasi Nasional, 2021)
This study aims to determine: (1) The influence of Work Environment on Employee Loyalty; (2) Effect of Compensation on Employee Loyalty; (3) The Effect of Work Environment and Compensation Against Employee Loyalty in PT. Nawakara Arta Kencana. Data collection methods in this study using questionnaires spread with the number of respondents 45 employees. Data analysis technique in this research using normality test, multicolinearity test, heteroscedasticity test, partial test (t test), and simultaneous test (f test). The results of this study indicate that: (1) Working Environment variables have an effect on significant to employee loyalty variable with t value> t table (2,972> 2,016); (2) Compensation variable significantly influence Employee Loyalty variable with t value> t table (5,500> 2,016); and (3) Work Environment Variables and Compensation Variables together affect Employee Loyalty variable in test result showing that the value of f arithmetic> f table (20,343> 3,21) and value of determination coefficient (R2) equal to 0, 492 or equal to 49 , 2%, it means that Work Environment variable and Compensation variable simultaneously influence Employee Loyalty variable as much 49,2%.